2021
DOI: 10.1177/1753425921995577
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free DNA, peripheral lymphocyte subsets alterations and neutrophil lymphocyte ratio in assessment of COVID-19 severity

Abstract: Cell destruction results in plasma accumulation of cell-free DNA (cfDNA). Dynamic changes in circulating lymphocytes are features of COVID-19. We aimed to investigate if cfDNA level can serve in stratification of COVID-19 patients, and if cfDNA level is associated with alterations in lymphocyte subsets and neutrophil-to-lymphocyte ratio (NLR). This cross-sectional comparative study enrolled 64 SARS-CoV-2-positive patients. Patients were subdivided to severe and non-severe groups. Plasma cfDNA concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 41 publications
4
22
1
Order By: Relevance
“…The diagnosis of COVID-19 was confirmed in all cases. The studies were conducted in China [ 8 13 , 15 , 16 , 18 , 19 , 21 – 23 , 25 , 31 34 ], Pakistan [ 28 ], Argentina [ 20 ], Turkey [ 14 , 17 , 33 , 35 ], Saudi Arabia [ 24 ], Iran [ 27 , 36 ], and Egypt [ 29 , 30 ]. The studies were conducted at a single center, with the exception of two multicenter studies [ 12 , 13 , 24 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of COVID-19 was confirmed in all cases. The studies were conducted in China [ 8 13 , 15 , 16 , 18 , 19 , 21 – 23 , 25 , 31 34 ], Pakistan [ 28 ], Argentina [ 20 ], Turkey [ 14 , 17 , 33 , 35 ], Saudi Arabia [ 24 ], Iran [ 27 , 36 ], and Egypt [ 29 , 30 ]. The studies were conducted at a single center, with the exception of two multicenter studies [ 12 , 13 , 24 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted at a single center, with the exception of two multicenter studies [ 12 , 13 , 24 , 34 ]. Two studies were prospective [ 11 , 26 ], two were cross-sectional [ 28 , 29 ], and the rest were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…In another study that set out to examine a means to discern severe cases, the NLR, WBC, NEU, LYM, CRP, and ferritin AUC was 0.831, 0.693, 0.765, 0.737, 0.816, and 0.752, respectively [24]. Other researchers observed an AUC for NLR and LYM of 0.98 and 0.092, respectively [25]. We found that the IG and IGLR values could reliably discriminate severe COVID-19 cases.…”
Section: Discussionmentioning
confidence: 96%
“…One study demonstrated that patients with severe COVID-19 infections had greater increases in cfDNA than those with milder disease; this may in large part be related to a correlation between intensity of inflammation and the magnitude of cfDNA increase. 16 The assay used in our study is specific for host ncfDNA and unlike other fluorometric or spectrophotometry based DNA quantification methods is not affected by DNA derived from exogenous sources such as bacteria, viruses or fungus. Increasing evidence suggests that cfDNA itself may be an actively released component of the damage-associated molecular pattern (DAMP) signaling pathway.…”
Section: Discussionmentioning
confidence: 99%